Exploring Discursive Strategies to Represent Power In The 2020 Final Presidential Debate between Donald J. Trump and Joe Biden: A Political Discourse Analysis - Cinta Invia Wulandari; Rini Afrilesa; Vera Magria (Krinok:Jurnal Linguistik Budaya, 2022)
Exploring Discursive Strategies to Represent Power in The 2020 Final Presidential Debate between Donald J. Trump and Joe Biden is a study that  analyzes the topic of political discourse, particularly focusing on discursive strategies used by the two presidential candidates. This research aims (1) to analyze the discursive strategies used by Donald Trump and Joe Biden in the final presidential debate; (2) to recognize the influence that these discursive strategies have on the 2020 final election results. The research applied a descriptive qualitative method, with the debate video as the data source. The data were utterances in the form of both candidates' words, phrases, and sentences. After being collected, the data were categorized and further analyzed based on Van Dijk’s approach of CDA (2003), in which he proposed 25 categories of discursive strategies in political discourse.The result of the study reveals some findings: First, out of 299 data of discursive strategies found in the debate, Donald Trump used 159 discursive strategies throughout the entire debate, with repetition as the most dominant one which was applied 17 times. Moreover, he did not apply any consensus and euphemism strategies. Meanwhile, Joe Biden only used 140 discursive strategies, with the number game as the most dominant strategy which appeared 20 times and he did not apply hyperbole in his utterances. Second, the writer found out that the two patterns of discursive strategies  influenced the 2020 US Presidential Election: (1) frequency and effectiveness of using discursive strategies; (2) the representation of power that focused more on displaying the negative sides of opponents have a higher chance of winning an election.